Comparison of supplier quality assurance methods for compound feed manufacturing from efficiency, product consistency and economical point of view - Csikai, Andrea (Acta Agraria Debreceniensis, 2010)
Feed manufacturing and human food production are the main routes of use for agricultural products. The food industryparticularly has intensively implemented the recent quality management principles and developed systems that facilitate the continuous improvement and efficiency of the industrial production. Feed production has taken similar approaches however the intensity of deployment at the manufacturer and the rollout towards its supply chain has shown slower progress. The methods, that the feed manufacturer manages the supplier chain of mainly primer agricultural products according to, have a certain impact on the efficiency of the inbound operations, feed product quality and its consistency as well as on other resources. These methods have been built on sound quality management principles that are stated not only in quality standards but also in relevant regulations. Current study addresses the questions related to the link between supply chain quality management and feed product. The objective of the frontier research was to highlight the  theoretical possibilities and benefits of the robust design methodimplemented into animal feed manufacturing dealing with highly variable ingredients.